Compensatory Education for Disadvantaged Students : Evidence from an Impact Evaluation Study in Mexico - Patrinos, Harry Anthony; Shapiro, Joseph; Moreno Trevino, Jorge (World Bank, Washington, DC, 2012)
Effectively educating all citizens is difficult in a geographically disperse and culturally heterogeneous country such as Mexico. How should Mexico educate the type of students who speak no Spanish, live in villages inaccessible by roads, or come from families that cannot afford school uniforms? Mexico began to address this challenge as early as 1971 by creating the National Council of Education Promotion (CONAFE), a division of Mexico's Secretariat of Public Education (SEP). CONAFE provides extra resources to schools that enroll disadvantaged students. CONAFE's compensatory education (see Box 1) programs now support more than three million students in pre-primary and primary education, and about one million students in telesecundaria education, or secondary education delivered via satellite television to remote schools. A recent evaluation of the impact of CONAFE's compensatory programs finds that CONAFE is most effective in improving primary school math learning and secondary school Spanish learning. Telesecundaria education and bilingual education for indigenous students are both shown to improve student achievement. CONAFE is also shown to lower primary school repetition and failure rates.